Teacher beliefs and practices: their effects on student achievement in the urban school setting - Herrera, John Christopher Sr. (Kansas State University, 2010)
Increasing diversity in schools in the United States over the last few decades, combined with an emphasis on high-stakes testing, has heightened concerns about the academic performance of students of color, in particular African American students. There are concerns about the appropriateness of a Eurocentric curriculum taught by White teachers, which often limits the use of a multicultural curriculum—one that values the culture and lifestyles of diverse students. This study focused on elements within teaching practices that improved achievement among students of color. An enhanced application of the Multiple Meanings of Multicultural Teacher Education Framework (MTEF), along with assessments of teacher training instruments (Gay, 1994; Love, 2001; Ladson-Billings, 1994), helped to create the Model for Modified Multicultural Teacher Education Framework on Teacher Perception of Student Achievement that served as a guide for the investigation. The overall findings confirmed the utility of the model and the enhancements made to the multicultural assessment instruments. Depending upon what elements were chosen, between 18% and 23% of the variance explained in teacher’s beliefs, attitudes and perceptions could be explained by their training, their community involvement, awareness of self, knowledge of subject and a positive approach to the institutional culture. The findings support the existing literature and adds to it a new dimension by directly focusing on teacher’s perceptions, attitudes and beliefs that promote or constrain teaching and learning about urban African American students in the urban classroom.
Keywords: teacher; beliefs; urban; achievement; multicultural; Education, Curriculum and Instruction (0727); Education, Secondary (0533); Education, Teacher Training (0530)